A reference specimen for compaction tests of fiber reinforcements. (2nd October 2019) - May, David; Kühn, Florian; Etchells, Matt; Fauster, Ewald; Endruweit, Andreas; Lira, Cristian
Abstract: Compaction behavior of textiles has a major influence on the outcome of various manufacturing processes for fiber reinforced polymer composites. Nevertheless, no standard exists up to date which specifies test methods or test rigs. A recent international benchmark revealed high variation associated with the result data. This work is a very first step toward a reference specimen, allowing for an isolated view on variations attributed to the test rig mechanics. A specimen design is proposed, intended to show compaction characteristics similar to technical textiles in terms of transverse compaction pressure and corresponding displacement. The reference specimen was tested in a round-robin study comprising test rigs at four different European research institutions. While reproducibility of the compaction behavior on each of the test rigs was high, clear variations between the results gained with different test rigs were observed. Graphical Abstract: